A place-based framework for assessing resettlement capacity in the context of displacement induced by climate change. (March 2022) - Walelign, Solomon Zena; Lujala, Päivi
Highlights: The article develops a conceptual framework to identify potential resettlement places for climate migrants. The framework focuses on livelihood reconstruction as a key to successful resettlement of people and communities. The framework's asset dimension captures the availability of different resources available the resettled. The condition dimension captures the factors that promote or constrain the use of assets in livelihood activities. The framework can assist policymakers when choosing the best places to resettle communities in the face of climate change. Abstract: Place-based resettlement capacity assessments to identify potential resettlement places for climate migrants are needed to guide resettlement programs related to climate change. This article proposes and validates a conceptual climate change resettlement capacity (CCRC) framework that can be used to identify potential resettlement places for climate migrants. The CCRC framework focuses on livelihood reconstruction, as this is the primary aim of most resettlement programs and a key for successful resettlement and mitigation of impoverishment of resettled people and communities. The framework has two main dimensions – assets and conditions – as its foundation, with a set of subdimensions and generic indicators identified for both of them. Expert evaluation was used to validate the framework. The operationalization of the framework is illustrated through a case study of two regions of Ethiopia vulnerable to climate change. The framework is designed to assist international organizations, governments, planners, and policymakers in identifying both the most suitable and least suitable places to resettle communities in the face of actual or anticipated displacements due to climate change. In addition, the framework can be used by researchers to undertake theoretical and empirical studies on resettlement induced by climate change. With minor modifications, the framework can also be applied to resettlement capacity assessments for non-climate resettlement programs and research.